Peningkatan Prestasi Belajar Matematika Materi Statistika melalui Metode Problem Based Instruction pada Siswa Kelas XII MIPA-5 di SMA Negeri 2 Cikarang Utara - Supriani Supriani; Supardi Supardi (PANDITA : Interdisciplinary Journal of Public Affairs, 2023)
In the problem-oriented teaching method it is assumed that student activity can be maximized, so that student performance can also increase. Therefore, this research was carried out with the aim of evaluating mathematics learning in statistics material using the problem based instruction method for class XII MIPA-5 students. This research was conducted at SMA Negeri 2 Cikarang Utara, which is located on Jalan Raya Lemahabang, Simpang Village, Kec. North Cikarang. This research began with a preliminary study from October to November 2021. The research subjects were all students of class XII MIPA-5 at SMA Negeri 2 Cikarang Utara in the odd semester of the 2021/2022 Academic Year, totaling 36 students. The results of the research show that the problem based instruction method does not only improve learning and student achievement. By applying the problem based instruction method, student learning can be improved, which is proven (1) to cause an increase in the level of completeness, during the pre-cycle it increased from 56% to 75% in cycle I and increased to a level in cycle II. 92%, (2) the level of incompleteness decreased, namely in the pre-cycle period it fell from 44% to 25% in Cycle I and to 8% in Cycle II, (3) the class average increased from 67 in the previous period. increased to 73 in Cycle I and 76 in Cycle II. With these results, the problem based instruction method is effective in improving student performance.